On the taxonomy of the dityline genera Diasclera Reitter, Dityloidea Fairmaire and Germain and Nerdanus Fairmaire (Coleoptera: Oedemeridae) - Švihla, Vladimír (Zootaxa, 2007)
New data on the taxonomy of three dityline genera are given. The genera Dityloidea Fairmaire and Germain, 1863 with the type species Dityloidea janthina Fairmaire and Germain, 1863, and Nerdanus Fairmaire, 1897 with the type species Nerdanus coeruleus Fairmaire, 1897 are redescribed and illustrated, their classification in the tribe Ditylini is stated and their relationships are discussed. A new subjective synonym: Diasclera Reitter, 1913 = Eumecomera Arnett, 1951, syn. nov. is proposed. Diasclera bicolor (Horn, 1870), comb. nov., D. cyanipennis (Horn, 1870), comb. nov. and D. obscura (Le Conte, 1854), comb. nov. are transferred to Diasclera from the genus Eumecomera and their distribution is discussed.